Heavy metal content and mobility in urban soils of public playgrounds and sport facility areas, Poland. (December 2018) - Różański, Szymon Łucjan; Kwasowski, Wojciech; Castejón, Jose Matias Peñas; Hardy, Amber
Abstract: Among the threats to air, soil, and water posed by urbanization, heavy metals appear particularly hazardous. Playgrounds and sport facilities are unique urban places, widely used by children and youth. The aim of this research was to evaluate heavy metal pollution in urban soils, identify relationships among topsoil metal distributions, and assess related health risks in two Polish cities – Warsaw and Bydgoszcz. According to the Regulation of the Polish Minister of the Environment guidelines for total content of Pb, Cu, Zn, Ni, Cd and Co our study sites were classified as uncontaminated. Applied Geoaccumulation Index ( I geo ; Müller, 1969) largely confirmed this classification, with only two of the investigated Warsaw areas "moderately polluted" with Pb. Generally, only Pb and Zn concentrations exceeded reference background levels for Polish soils. The highest concentrations of Pb and Zn were found in the city centers, the oldest areas where pollution risk is potentially the highest. Metal mobility and solubility were mainly correlated with total content, indicating potential risk from lead and zinc. At some sites in Warsaw, where mean Pb concentration was 87.25 mg kg −1 and Zn 207.25 mg kg −1, health risks from ingestion and inhalation seemed significant, particularly for children. In Bydgoszcz use of the studied playgrounds and sport facility areas did not pose a risk to human health. Finally, the study (especially in Warsaw) indicates the need for continued monitoring and suggests lowering permissible limits of these metals in soils, especially in recreational areas, may decrease childrens' exposure risk to these pollutants. Highlights: Urban soils of playgrounds and sport facilities are special places in the cities. The main source of metals was atmospheric deposition. Concentrations of Pb and Zn indicates potential human health risk. Metal solubility and mobility were correlated with the total content. The study indicated the need for lowering the permissible limits of metals.